Quintuña Suarez,Ginger Mindy(2023)NIVELES DE FERTILIZACIÓN CON UREA EN LA PRODUCCIÓN FORRAJERA Y COMPOSICIÓN QUÍMICA DE Erythrina poeppigiana EN LA ALIMENTACIÓN ANIMAL.Quevedo.UTEQ.65p. - Quintuña Suarez , Ginger Mindy (2023)
This research was carried out on the grounds of the Quevedo State Technical University, on the "La María" campus (Rumiology Laboratory). This study was aimed at evaluatingthe different doses of nitrogen on Erythrina poeppigiana on agronomic behavior and bromatological composition, during the dry season. The evaluated treatments were: nitrogen doses (T0: 0 kg N ha-1 cut-1; T1: 100 kg N ha-1 cut-1; T2: 200 kg N ha-1 cut-1 and T3: 300 kg N ha-1 cut-1) with 4 repetitions. A completely randomized design (DCA) was used. The variables were analyzed using the Tukey test (P<0.05). The agronomic behavior was evaluated: plant height (AP); sheet weight (PH); stem weight (PT); leaf/stem ratio (R H/T) and biomass. For the bromatological composition: dry matter (DM); organic matter (OM); crude protein (CP); neutral detergent fiber (NDF) and acid detergent fiber (FDA). Nitrogen doses did not influence (P>0.05) the AP variables; PH; PT; RH/T; biomass, DM; MO; NDF and FDA. The highest (P<0.05) PC was recorded by treatments T3 and T2 (24.03 and 24.00%). The use of nitrogenous sources directly influences the quality of the PC.